PENINGKATAN KEMAMPUAN MENULIS CERPEN DENGAN MEDIA VIDEOKLIP PADA SISWA KELAS IX F SMP NEGERI 2 KALITIDU BOJONEGORO - Susiana Susiana (EDU-KATA, 2014)
The aim ofthe research was to describe theimplementation of learning to write short story using video clips. The research sources of the data from the teachers and studentsactivities, students response, and the result of the studentsin writing short story in class IX-F SMP Negeri 2 Kalitidu Bojonegoro. Based on the research to collected data by using test and nontest.The research showed thatThe teacher activity increased by 13.4%.Student activity increased 6.6%. Overall response to increased student learning to write short stories by using videoclips. The studentslearningoutcomes also increaseby19.8%. The average of class in thefirst cycle value of 62.5 and for the second cycle has the average classincrease 82.3. Increasing student competence in writing short stories also followed by a behavioral change towards the better. The students become more focused in the following lesson.